Recall and retention of L2 to L1 word translation equivalents via subvocalization among weak Malaysian learners / Albert Wilson Eng Hock - Wilson Eng Hock, Albert (2009)
Effective word recall and retention is important in vocabulary learning. Therefore, there is a tendency that weak learners may memorize the meaning of an L2 word through its L1 translation equivalent as an effective word recall leaning technique. This quasi—experimental study examined the effectiveness of these leaners’ ability to recall the Malay language translation equivalents (L1) of English words (L2) via rote memorization technique. Two different groups of non native English speakers at age thirteen were compared in the written word recall tests. In the first group (SV), the subjects were given 15 seconds to memorize sub-vocally each of the twenty L2 to L] word translation equivalent pairs whereas for the other group, the control group (NSV), the subjects were not allowed to memorize the same word pair list. In both groups the subjects were to write the Malay language translation equivalents of the English words in a word recall test immediately after instruction and seven days later. There was no significant difference in the ability of the subjects to recall between the two groups and the effect of time was also insignificant. This finding is interpreted as evidence that the use of translation equivalents through rote learning and sub-vocalization is inadequate for word recall and retention among weak non-native speakers. This study also explored whether these learners were able to recall syntagmatic or paradigmatic word structure better than the other. Results, taken from the data above, showed that there was no significant difference in the type of words recalled across the two different time periods. This implies that these learners have no preference over any of these two word structures that they can recall and retain effectively in L2 vocabulary teaching and learning.